Research progress on transcranial magnetic stimulation for post-stroke dysphagia - Li, Yi; Chen, Kerong; Wang, Jiapu; Lu, Hanmei; Li, Xiaoyu; Yang, Lei; Zhang, Wenlu; Ning, Shujuan; Wang, Juan; Sun, Yi; Song, Yu; Zhang, Mei; et al. (Frontiers in Behavioral Neuroscience, 2022)
Dysphagia is one of the most common manifestations of stroke, which can affect as many as 50-81% of acute stroke patients. Despite the development of diverse treatment approaches, the precise mechanisms underlying therapeutic efficacy remain controversial. Earlier studies have revealed that the onset of dysphagia is associated with neurological damage. Neuroplasticity-based transcranial magnetic stimulation (TMS), a recently introduced technique, is widely used in the treatment of post-stroke dysphagia (PSD) by increasing changes in neurological pathways through synaptogenesis, reorganization, network strengthening and inhibition. The main objective of this review is to discuss the effectiveness, mechanisms, potential limitations, and prospects of TMS for clinical application in PSD rehabilitation, with a view to provide a reference for future research and clinical practice.